Analisa Pengaruh Pendingin Terhadap Struktur Mikro Dan Sifat Mekanik Pada Baja ST 60 - Siagian, Parulian; Nababan, Wilson Sabastian; Manurung, Charles S.P; Lumbangaol, Partahi; Siagian, Lestina; Manurung, Wany Chytra (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2024)
The field of industry that produces human needs is growing rapidly. Encouraging increased productivity with iron metal-based machine components. Using quality materials, and certified. This research uses ST 60 steel with a carbon content of 0.48%.. The research process that will be carried out is Heat treatment is needed to minimize failure, change the structure, and form the desired properties, the rapid cooling process to produce a comparison of hardness in material variations, hardness testing to determine the hardness of a material, and observation of microstructure to observe the type of microstructure formed after heat treatment and without heat treatment. After testing, the heat treatment process greatly affects changes in the mechanical properties of the material, as evidenced by the increase in hardness values which initially before the heat treatment process amounted to 194.6 Kgrf / to 255.53 Kgrf / with SAE 40 lubricant cooling media, 220.43 Kgrf / with 50% lubricant cooling media with 50% water mixture, and 300, 7 Kgrf/ with long life coolant media and it is proven that in each material given heat treatment the hardness value has increased as well, before heat treatment the hardness value in ST 60 steel is only 194.6 Kgrf/, experiencing an increase in mechanical properties, namely work with SAE 40 lubricant cooling media with a value of 255.53 Kgrf/, 50% lubricant cooling media with 50% water mixture worth 220.43 Kgrf/ and long life coolant of 300.7 Kgrf/.